Exercise

$2\cdot log\left(x\right)-1\cdot log\left(x+6\right)=0$

Step-by-step Solution

1

Apply the formula: $a\log_{b}\left(x\right)$$=\log_{b}\left(x^a\right)$

$\log \left(x^2\right)-\log \left(x+6\right)=0$
2

The difference of two logarithms of equal base $b$ is equal to the logarithm of the quotient: $\log_b(x)-\log_b(y)=\log_b\left(\frac{x}{y}\right)$

$\log \left(\frac{x^2}{x+6}\right)=0$
3

Rewrite the number $0$ as a logarithm of base $10$

$\log \left(\frac{x^2}{x+6}\right)=\log \left(1\right)$
4

For two logarithms of the same base to be equal, their arguments must be equal. In other words, if $\log(a)=\log(b)$ then $a$ must equal $b$

$\frac{x^2}{x+6}=1$
5

Multiply both sides of the equation by $x+6$

$x^2=x+6$
6

Move everything to the left hand side of the equation

$x^2-x-6=0$
7

Factor the trinomial $x^2-x-6$ finding two numbers that multiply to form $-6$ and added form $-1$

$\begin{matrix}\left(2\right)\left(-3\right)=-6\\ \left(2\right)+\left(-3\right)=-1\end{matrix}$
8

Rewrite the polynomial as the product of two binomials consisting of the sum of the variable and the found values

$\left(x+2\right)\left(x-3\right)=0$
9

Break the equation in $2$ factors and set each factor equal to zero, to obtain simpler equations

$x+2=0,\:x-3=0$
10

Solve the equation ($1$)

$x+2=0$
11

We need to isolate the dependent variable $x$, we can do that by simultaneously subtracting $2$ from both sides of the equation

$x+2-2=0-2$
12

Canceling terms on both sides

$x=-2$
13

Solve the equation ($2$)

$x-3=0$
14

We need to isolate the dependent variable $x$, we can do that by simultaneously subtracting $-3$ from both sides of the equation

$x-3+3=0+3$
15

Canceling terms on both sides

$x=3$
16

Combining all solutions, the $2$ solutions of the equation are

$x=-2,\:x=3$

Verify that the solutions obtained are valid in the initial equation

17

The valid solutions to the logarithmic equation are the ones that, when replaced in the original equation, don't result in any logarithm of negative numbers or zero, since in those cases the logarithm does not exist

$x=3$

Final answer to the exercise

$x=3$

Try other ways to solve this exercise

  • Choose an option
  • Solve for x
  • Find the derivative using the definition
  • Solve by quadratic formula (general formula)
  • Simplify
  • Find the integral
  • Find the derivative
  • Factor
  • Factor by completing the square
  • Find the roots
  • Load more...
Can't find a method? Tell us so we can add it.
Symbolic mode
Text mode
Go!
1
2
3
4
5
6
7
8
9
0
a
b
c
d
f
g
m
n
u
v
w
x
y
z
.
(◻)
+
-
×
◻/◻
/
÷
2

e
π
ln
log
log
lim
d/dx
Dx
|◻|
θ
=
>
<
>=
<=
sin
cos
tan
cot
sec
csc

asin
acos
atan
acot
asec
acsc

sinh
cosh
tanh
coth
sech
csch

asinh
acosh
atanh
acoth
asech
acsch

Your Personal Math Tutor. Powered by AI

Available 24/7, 365 days a year.

Complete step-by-step math solutions. No ads.

Choose between multiple solving methods.

Download unlimited solutions in PDF format.

Unlimited practice with our AI whiteboard.

Premium access on our iOS and Android apps.

Join 500k+ students in problem solving.

Choose your plan. Cancel Anytime.
Pay $39.97 USD securely with your payment method.
Please hold while your payment is being processed.

Create an Account